Antecedents and consequences of caregiving structure on young mothers and their infants. - Arnold, Anna; Lewis, Jessica; Maximovich, Alexey; Ickovics, Jeannette; Kershaw, Trace (Maternal and child health journal, 2011)
This study describes the multigenerational caregiving structure of infants born to young women, the prenatal predictors of caregiving structure, and the effects of caregiving structure on the health of young mothers and their infants 6 months postpartum. The sample consisted of 784 young mothers involved in a longitudinal study in two U.S. cities. Women were classified into eight caregiving structure groups based on the mother's report of herself as a caregiver and her selection of the baby's father and/or grandparents as caregivers. ANCOVA analyses identified predictors and 6 month postpartum outcomes of caregiving structure. Planned comparisons explored the relationships among caregiving structure groups. A majority of women reported caregiving structures other than herself and the father as caregivers (87.1%). Grandparents were indicated as caregivers by most women (62.2%). Postpartum caregiving groups differed on prenatal social support, self-esteem, attachment avoidance and anxiety, relationship status, and living with the baby's father. While mother's self esteem significantly predicted father involvement, there were no differences on predictors between when the mother and father were caregivers, versus when the mother and grandparents were caregivers. Differences existed between groups on mother and child outcomes, including parenting stress, distress, and child dysfunction. Women reported significantly less parenting stress, child dysfunction, and negative child emotions when she and the father were caregivers, versus when she and grandparents were caregivers. The family system and the intergenerational dynamics within a multigenerational caregiving structure are critical to the health and well-being of both mothers and their children.
Keywords: Adolescent; Adult; Caregivers; Connecticut; Family Characteristics; Family Relations; Female; Georgia; Humans; Intergenerational Relations; Interviews as Topic; Parenting; Pregnancy; Pregnancy in Adolescence; Questionnaires; Young Adult